TNF inhibitors affect the induction and maintenance of spike-specific B-cell responses after mRNA vaccination - Sander W Tas; Taco W Kuijpers; Gertjan Wolbink; Theo Rispens; Anja Ten Brinke; Juan J Garcia-Vallejo; S Marieke van Ham; Mark Löwenberg; Luuk Wieske; Laura Boekel; Filip Eftimov; Eileen W Stalman; et al. (RMD Open)
Objectives Tumour necrosis factor inhibitors (TNFi) are widely used and effective as treatment for immune-mediated inflammatory diseases (IMIDs). However, TNFi therapy causes a faster waning of antibody responses following vaccination. The underlying cause by which TNFi affect humoral immunity remains to be elucidated. The formation of long-lasting, high-affinity antibodies after vaccination results from germinal centre (GC)-derived, T cell-dependent B-cell responses. Therefore, this study investigated how TNFi affect the formation and maintenance of antigen-specific B- and CD4+ T-cell responses following SARS-CoV-2 mRNA vaccination.Methods SARS-CoV-2 spike-specific B-cell responses were characterised using spectral flow cytometry. Spike-specific CD4+ T cells were measured using an activation-induced marker assay. 15 patients with inflammatory bowel disease (IBD) treated with TNFi were compared with 9 IBD patients without systemic immunosuppression and 10 healthy controls.Results Spike-specific CD4+T-cell frequency and phenotype, including T follicular helper cells, were not affected by TNFi. Total spike-specific B-cell frequencies were reduced in TNFi-treated patients. Deep phenotyping revealed lower IgG+memory B-cell frequencies in TNFi-treated patients 3–6 months after vaccination. These data were confirmed in TNFi-treated rheumatoid arthritis patients. Interestingly, already at day 7 after the second vaccination, TNFi therapy reduced the induction of class-switched CD11c- CD71+activated B cells, which are believed to be GC-derived. Conversely, CD11c+B cells, associated with extrafollicular B-cell responses, were not affected by TNFi therapy.Conclusions These data suggest that TNFi therapy affects the differentiation of GC-derived B cells, which may explain its effect on humoral immune responses.